2022
DOI: 10.3390/jof8101050
|View full text |Cite
|
Sign up to set email alerts
|

An Endoglucanase Secreted by Ustilago esculenta Promotes Fungal Proliferation

Abstract: Ustilago esculenta is a fungus of two morphological forms, among the filamentous dikaryon that can induce the plant stem to expand to form fleshy stem. In order to establish biotrophy with Zizania latifolia which belongs to the tribe Oryzeae (Poaceae), U. esculenta firstly needs to secrete a bunch of effectors, among them being cell wall degrading enzymes (CWDEs). We have isolated a gene, UeEgl1, which was differentially expressed in MT-type and T-type U. esculenta at an early stage of infection, and specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Results showed that the content of xylose is much higher than glucose or other monosaccharides, indicating that xylan is the most important component of the plant cell wall ( Figure 4 C). The functional study of endoglucanases during the infection process is discussed by Zhang et al [ 40 ]. Knock-out of one endoglucanase did not affect haploid growth but will slow down the infection process and attenuate the final symptom.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the content of xylose is much higher than glucose or other monosaccharides, indicating that xylan is the most important component of the plant cell wall ( Figure 4 C). The functional study of endoglucanases during the infection process is discussed by Zhang et al [ 40 ]. Knock-out of one endoglucanase did not affect haploid growth but will slow down the infection process and attenuate the final symptom.…”
Section: Resultsmentioning
confidence: 99%
“…A few functions such as teliospore formation, germination, and the whole haploid life degenerate in MT-type U. esculenta . Recently, several studies have reported functional degeneration in the secretion of plant cell wall degrading enzymes and effectors, which are crucial for penetrating plant cuticles ( Wang et al, 2022 ; Zhang et al, 2022 ). In contrast, MT-type maintains the functioning of karyogamy.…”
Section: Discussionmentioning
confidence: 99%
“…10. 3389/fmicb.2023.1199907 Frontiers in Microbiology frontiersin.org cuticles (Wang et al, 2022;Zhang et al, 2022). In contrast, MT-type maintains the functioning of karyogamy.…”
Section: Discussionmentioning
confidence: 99%
“…Latest research associates GH45 enzymes with pathogenic pathways, invoking plant immune response, but possible involvement in fungal cell developmental processes cannot be disregarded, as an upregulation of a GH45 enzyme has promoted fungal cell proliferation in Ustilago esculenta (X. Guo et al, 2022;Zhang et al, 2022).…”
Section: Glycoside Hydrolase Family 45mentioning
confidence: 99%